Partição e destino metabólico do 14C-glicerol dietético em tecidos-alvo de juvenis de tilápia - Costa, Diego Vicente da (2015)
Aquaculture, as opposed to stagnating extractive fish production, has greatly developed worldwide in recent years and may benefit from the current excess of glycerol in the biodiesel market. Glycerol may be used as an energy source in fish diet as alternative to the conventional sources used. This study discusses in Chapter 1 some aspects related to the availability of this nutrient in the market, the use and the metabolism of dietary glycerol in fish, as well as the theoretical basis of the experimental techniques used in Chapter 2. This last chapter aimed to evaluate how the inclusion of glycerol in diets for tilapia (Oreochromis mossambicus) could affect the juveniles metabolism and how the fish use this new ingredient. The experimental diets were formulated to contain 0% (G0), 5% (G5) and 15% (G15) of purified glycerol and were provided for 40 days to apparent satiation, 3 times a day. For the metabolism trials, six fish from each treatment were randomly chosen and force-fed with five pellets unitarily labeled with known radioactivity rates of 14C-glycerol ([14C(U), 9.25MBq, Perkin Elmer, USA). It was evaluated the nutrient digestibility, catabolism, retention and partition of the nutrient in the muscle and liver. There were no differences between treatments for 14C-glycerol absorption and evacuation. The treatment G5 presented the highest percentage of 14C-glycerol retention and the lowest percentage of catabolism. There was no difference for total 14C-lipid and 14C-protein. Compared to other treatments, treatment G5 presented the highest radioactivity counting in the non-lipid and non-protein extract. Treatment G0 presented the highest level of 14C-lipid in muscle, however no differences were found in fish liver. Treatment G15 presented the lowest level of 14C-protein in muscle, however no differences were found between treatments in fish liver. The non-lipid and non-protein fraction presented the highest radioactivity counting in the liver of fish from treatment G5, however there were no differences in fish muscle. Juveniles tilapia are able to metabolize the 14C-retained glycerol into lipid, protein and carbohydrate, in both liver and muscle. Dietary glycerol may be an effective energy source for tilapia juveniles, according to the inclusion levels studied.